2021
DOI: 10.3390/f12070862
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Stocks in Miombo Woodlands: Evidence from over 50 Years

Abstract: Miombo woodlands are extensive dry forest ecosystems in central and southern Africa covering ≈2.7 million km2. Despite their vast expanse and global importance for carbon storage, the long-term carbon stocks and dynamics have been poorly researched. The objective of this paper was to present and summarize the evidence gathered on aboveground carbon (AGC) and soil organic carbon (SOC) stocks of miombo woodlands from the 1960s to mid-2018 through a literature review. We reviewed the data to find out to what exte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Williams et al (2008) stated that the clearance for agriculture could reduce the loss of stem wood carbon stocks. Also, Bulusu et al (2021) and Gumbo et al (2018) found that deforestation in miombo woodlands was driven by land clearance, and grassland and forest were cleared for agriculture and wood extraction for energy. These land transitions led to a decrease in carbon stored across miombo woodlands (Jew et al 2016).…”
Section: Analysis Of Carbon Storage Changementioning
confidence: 99%
“…Williams et al (2008) stated that the clearance for agriculture could reduce the loss of stem wood carbon stocks. Also, Bulusu et al (2021) and Gumbo et al (2018) found that deforestation in miombo woodlands was driven by land clearance, and grassland and forest were cleared for agriculture and wood extraction for energy. These land transitions led to a decrease in carbon stored across miombo woodlands (Jew et al 2016).…”
Section: Analysis Of Carbon Storage Changementioning
confidence: 99%